Detection of ganciclovir resistance mutations by pyrosequencing in HCMV-infected pediatric patients - Benzi, Fabio; Vanni, Irene; Cassina, Giulia; Ugolotti, Elisabetta; Di Marco, Eddi; Cirillo, Carmela; Cristina, Emilio; Morreale, Giuseppe; Melioli, Giovanni; Malnati, Mauro; Biassoni, Roberto (Journal of clinical virology, 2012)
Human cytomegalovirus (HCMV) is an opportunistic pathogen especially for immuno-suppressed subjects that might develop pharmacological resistance in patients undergoing prolonged antiviral treatment. Ganciclovir (GCV) is the drug used as first choice therapy in affected children and a GCV-resistant phenotype is mainly linked to mutations of the viral protein kinase UL97. Here a new quantitative pyrosequence (PSQ) method is presented that allows detection and quantification of the viral species carrying the more frequent UL97 mutations responsible for GCV resistance in clinical samples (>80% of known cases). The system has been validated using two independent approaches (cloning and sequencing of UL-97 gene fragments and real-time PCR) and clinical samples derived from 3 pediatric patients. The UL97 pyrosequencing analysis has indicated a significant increase of mutant viruses carrying the H520Q and C592G mutations. In particular, the H520Q viral mutation, known to increase GCV resistance (IC50=10) increased around 5 times during hospitalization. In addition, C592G (known to have IC50=2.9) also increased 3 times. PSQ is a quick, cheap, high throughput and sensitive analysis method to detect GCV-associated resistance mutation useful to follow antiviral therapy in perinatal CMV-infection as well as in immune-suppressed patients.